Viral Activation of Heparanase Drives Pathogenesis of Herpes Simplex Virus-1 - Agelidis, Alex M. (Cell Rep, 2017)
Herpes simplex virus type-1 (HSV-1) causes lifelong recurrent pathologies without a cure. How infection by HSV-1 triggers disease processes, especially in the immune-privileged avascular human cornea, remains a major unresolved puzzle. It has been speculated that a cornea-resident molecule must tip the balance in favor of pro-inflammatory and pro-angiogenic conditions observed with herpetic as well as non-herpetic ailments of the cornea. Here, we demonstrate that heparanase (HPSE), a host enzyme, is the molecular trigger for multiple pathologies associated with HSV-1 infection. In human corneal epithelial cells, HSV-1 infection upregulates HPSE in a manner dependent on HSV-1 infected cell protein 34.5. HPSE then relocates to the nucleus to regulate cytokine production, inhibits wound closure, enhances viral spread, and thus generates a toxic local environment. Overall, our findings implicate activated HPSE as a driver of viral pathogenesis, and call for further attention to this host protein in infection and other inflammatory disorders.